Conflicts of Interest? The Ethics of Usury - Lewison, Martin (Journal of business ethics, 1999)
Social attitudes toward usury (here defined using the archaic meaning as the taking of interest on loans) have changed dramatically over the centuries. From antiquity until the Protestant Reformation, usury was regarded as an inherently evil activity. Today, with few exceptions, usury is met with moral indifference. Modern objections to usury are limited to protest against "excessive" interest rates rather than interest per se. With this change in focus, the very meaning of the term "usury" has also changed. Many early pronouncements against the taking of interest emphasized the plight of the poor, but ironically, the poor actually pay the highest rates of interest in the modern American economy. Despite the universality of usury, some socio-economic subcultures still manage to avoid the taking or giving of interest. Orthodox branches of both Judaism and Islam have maintained bans on usury throughout the centuries and up to the present time. This is especially interesting in the case of Judaism, given the popular cultural image of the Jew as usurer. Jewish free loan systems may actually offer a model for modern loan programs that can be designed to aid poor borrowers, who are frequently shut out of mainstream financial services.